Probabilistic modeling of flood characterizations with parametric and minimum information pair-copula model - Daneshkhah, Alireza; Remesan, Renji; Chatrabgoun, Omid; Holman, Ian P. (Elsevier, 2016)
This paper highlights the usefulness of the minimum information and parametric pair-copula construction (PCC) to model the joint distribution of flood event properties. Both of these models outperform other standard multivariate copula in modeling multivariate flood data that exhibiting complex patterns of dependence, particularly in the tails. In particular, the minimum information pair-copula model shows greater flexibility and produces better approximation of the joint probability density and corresponding measures have capability for effective hazard assessments. The study demonstrates that any multivariate density can be approximated to any degree of desired precision using minimum information pair-copula model and can be practically used for probabilistic flood hazard assessment.
Keywords: Flood frequency analysis; Flood hazard characterization; Return period; D-vine model; Minimum information pair-copula model; Himalaya (India)